2016
DOI: 10.4178/epih.e2016017
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting screening for diabetic complications in the community: a multilevel analysis

Abstract: OBJECTIVES:The objective of the present study was to identify the factors that affect screening for diabetic complications by sex in the community.METHODS:This study used individual-level data from the 2013 Community Health Survey (CHS) for 20,806 (male, 9,958; female, 10,848) adults aged 30 years or older who were diagnosed with diabetes. Community-level data for 253 communities were derived from either CHS or national statistics. A chi-square test and multilevel logistic regression analysis was performed.RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…In a previous study that used 2013 KCHS data [ 24 ], the number of internists per 1000 inhabitants was positively related to undergoing a fundus examination or microalbuminuria test (OR 1.26, 95% CI 1.01–1.57), and this effect size was smaller than that in our study. The heterogeneity among districts explained by the district-level variable was greater in our study than in the previous study.…”
Section: Discussioncontrasting
confidence: 96%
“…In a previous study that used 2013 KCHS data [ 24 ], the number of internists per 1000 inhabitants was positively related to undergoing a fundus examination or microalbuminuria test (OR 1.26, 95% CI 1.01–1.57), and this effect size was smaller than that in our study. The heterogeneity among districts explained by the district-level variable was greater in our study than in the previous study.…”
Section: Discussioncontrasting
confidence: 96%
“…The results of this study showed that diabetic patients who responded that their subjective health were moderate or poor utilized both the fundus examination and microprotein urination more than those who indicated that their subjective health were good. Previous studies also confirmed this result ( 10 , 11 , 13 , 15 ). It could be because when people judged themselves healthier, their positive thoughts had a negative correlation with preventive health behaviors such as regular health checkups ( 11 , 15 ).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies also confirmed this result ( 10 , 11 , 13 , 15 ). It could be because when people judged themselves healthier, their positive thoughts had a negative correlation with preventive health behaviors such as regular health checkups ( 11 , 15 ). Therefore, it is needed that the primary medical care should provide regular notice and education about regular complication examination for diabetic patients who believe that they are in good health and monitor whether they utilize complication screening continuously.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is a disease that requires not only drug treatment but also self-management. Due to the aging of the population and the development of diagnostic and treatment technologies, the timing of diabetes diagnosis is accelerating, and the period to manage diabetes is lengthening, making it essential to develop more active self-management habits [35,36]. The subject of disease management is the patient.…”
Section: Discussionmentioning
confidence: 99%